KEPEMIMPINAN RELIGIUS DALAM MEMBANGUN UKHUWAH ISLAMIAH (STUDI KASUS PEMKOT MAKASSAR) - Laode Muhamad Fathun (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
This paper aims to explain how the strategy of the Government of Makassar in making the values of Islamiah in shaping ukhuwah in Makassar. By using the concept analisasi Buyda theory and the theory of leadership into a blade analysis the authors analyze the Government's strategy to form the Islamic brotherhood in Makassar. Simply how political intervention against Islamic phenomenon. With this type of analytic and descriptive writing techniques of secondary and primary data collection showed that the Government of Makassar using Islamic values that the dawn prayer with all its usefulness as a strategy to cultivate friendship rope while building morality ukhuwah in Makassar. Attended by thousands of local officials, private, school and university students as well as other public evidence of the seriousness of the government to make the dawn prayer in congregation as an instrument to build Makassar religious brotherhood. In this context when political control of religion done by leaders who transformative natara then there is no separation of Islam and politics, because the guidance of Islam is political, social, economic, and perfect law in society.